Creating a data processing warehouse to support performance monitoring of cancer screening programmes in Europe using a common set of indicators. - Lucas, Eric; Dimitrova, Nadya; Tomatis, Mariano; Sheridan, Brian; Arbyn, Marc; Heijnsdijk, Evelyne; Armaroli, Paola; Martens, Patrick; Partanen, Veli-Matti; Chandran, Arunah; Carvalho, Andre L; Yared, Wendy; et al. (European Journal of Public Health, 2025)
The CanScreen-ECIS project implemented by International Agency for Research on Cancer aimed to define indicators to monitor, breast, cervical, colorectal, and lung cancer screening and create a validated mechanism for the European screening programmes to be able to systematically collect and submit performance data for public dissemination through European Cancer Information System (ECIS). Indicators were developed through a stepwise process of literature review, Delphi survey followed by face-to-face interaction. A survey questionnaire to report policies, protocols, and organization of screening programmes and a data collection tool to estimate indicators across the screening continuum were designed. These were integrated into a data warehouse to permit programme managers to access the tools, undergo training, submit data, and estimate the indicators. The same warehouse would allow peer-reviewing of submitted information and data and will ultimately be connected to ECIS for data visualization. Functionalities of the tools and the warehouse were pilot tested through data collection from several European countries. Total 23 indicators were selected based on priority and feasibility. Programme managers from 23 European countries completed the surveys and submitted data from national/regional screening programmes. Data to estimate the indicators were obtained from 17, 13, and 15 breast, cervical, and colorectal cancer screening programmes, respectively. Major challenges identified by the participants included collecting data from opportunistic screening and data disaggregated by socio-economic status and other indicators of inequalities. The data warehouse will facilitate systematic data collection to report the status and performance of cancer screening programmes in the EU.